Screening for Hypertension in Children and Adolescents: Methodology and Current Practice Recommendations - Lewis, Michaela N.; Shatat, Ibrahim F.; Phillips, Shannon M. (Frontiers in Pediatrics, 2017)
Hypertension requires urgent, uniform, and consistent attention across all frontiers of pediatric health care not only because of established links between the onset of hypertension during one’s youth and its sustenance throughout adulthood, but also because of the sequelae associated with the disease’s trajectory, such as cardiovascular disease, end organ damage, and decreased quality of life. Although national guidelines for the diagnosis and management of pediatric hypertension have been available for nearly 40 years, knowledge and recognition of the problem by clinicians remain poor due to a host of influencing factors. The purpose of this article is to explicate key issues contributing to the inaccurate measurement of blood pressure and misclassification of hypertension among children and to present strategies to address these issues.